Enhancing decision-making skills in student groups: A theoretical and applied approach - Egerau , Anca Manuela; Torkos, Henrietta (Technium Social Sciences Journal, 2025)
Decision-making skills are essential for future educators, particularly for students specializing in Primary and Preschool Pedagogy. This study examines the practical impact of structured training interventions on the decision-making competencies of students enrolled at Aurel Vlaicu University of Arad. The research follows a mixed-methods approach, combining quantitative surveys and qualitative observations to assess students’ ability to analyze complex situations, weigh alternatives, and make informed decisions in an academic setting. The study sample consists of undergraduate students from the Faculty of Educational Sciences, Psychology, and Social Work, engaged in group-based learning activities designed to enhance their problem-solving and critical-thinking capabilities. The findings demonstrate practical improvements in students' confidence and efficiency in decision-making through active learning methodologies, including collaborative projects, case studies, and scenario-based discussions. Furthermore, the research highlights the role of peer interaction and reflective practice in fostering deeper cognitive engagement. These results have direct implications for curriculum design, proposing the integration of structured decision-making training as a core competency in teacher education programs.